Faktor-Faktor Yang Memengaruhi Biaya Riil Pada Pasien Jkn Ppok Rawat Inap Di RSUD Pandan Arang - Ratna Mildawati; Kristian Ubanayo (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease characterized by progressive airflow obstruction in the airways. COPD is a chronic condition for which the procedure financing is regulated in the INA-CBG’s tariff. This study aims to analyze the therapy costs for COPD patients, identify factors that affect the therapy costs for these patients, and evaluate the alignment between real costs and the INA-CBG’s tariff for inpatient COPD patients at RSUD Pandan Arang. This research is an analytical observational study with a cross-sectional approach from the hospital's perspective. The subjects of this study were inpatient COPD patients treated between January and August 2018. The data collection method was retrospective. The data used in this study is quantitative. The analysis of factors affecting real costs was performed using correlation analysis. The results of this study indicate that the average therapy costs for COPD patients in care classes 1, 2, and 3 at severity level I were Rp 3,197,754, Rp 2,182,918, and Rp 2,591,481, respectively, while for class 3 patients at severity level II, the therapy cost reached Rp 6,262,464. Additionally, a difference between the real costs and the costs calculated based on the INA-CBG’s tariff was found, with a total cost difference of Rp 36,933,898 for 61 patients. This discrepancy highlights the misalignment between the average real costs and the INA-CBG’s tariff, especially at severity level I for care class 1 and at severity level II for care class 3. Factors affecting real costs for COPD patients include secondary diagnoses and the length of stay (LOS).